Semper Aliquid Novi: Reclaiming the future of book history from an African perspective - McDonald, P (Johns Hopkins University Press, 2017)
The study of books has a complex genealogy that can be traced back at least to the nineteenth century, especially if we bear in mind the long history of British bibliography. Yet it was only when an international group of historians, literary scholars, bibliographers, sociologists and librarians began to coordinate their various activities in the 1960s and 1970s that the “history of the book” emerged as a distinct scholarly enterprise, and it was only in the following decade that it started to see itself as a discipline in the making.